Municipal cadres in Telangana - A case study - Rao, D.V. (2015)
Jawaharlal Nehru National Urban Renewal Mission (JNNURM) which was launched by Government of India during 2005 for integrated development of Urban Local Bodies (ULBs) envisaged infrastructural services and reforms. One of the reforms was creation of cadre of municipal staff for different disciplines and it was expected to lead (i) ULBs to have full- time staff with specialised skills within the hierarchy of municipal setup; (ii) clear career-growth path; and (iii) experience-sharing across cities through movement of personnel. Telangana State has been created as the 29th State in India in June, 2014. It has been carved out of Andhra Pradesh. The municipalities in Telangana are governed under Andhra Pradesh Municipalities Act, 1965. Well-established municipal cadres exist in Telangana. As per the Municipal Act, a municipality has to perform various functions through multiple functionaries. There is well-structured functional hierarchy (staff model) in the municipal system in the State. There are three services which cater to the personnel requirements of municipalities in Telangana, viz. (i) State Service, (ii) State Municipal Service, and (iii) Municipal Service. Under State Service, senior officers working in municipalities like Commissioner, Municipal Engineer, Municipal Health Officer and Town Planning Officer belong to this service. They work both in municipalities and government departments. Secondly, middle-level officers or employees of municipalities in the State are constituted as State Municipal Service with a common seniority to make them eligible for various posts in municipalities across the State. All other posts belong to Municipal Service. They are basically in the lower level of hierarchy and each Municipality is a unit of appointment. There is an organic linkage among the three Services. Further, Government has power to transfer any officer or employee of a municipality to the service of any other municipality. The reform contemplated under JNNURM aimed at creation of cadre of municipal staff for different disciplines in the state of Telangana and the outcomes expected of the reform are already in place in the State. - Reproduced.
Keywords: Local government - India - Telangana; Local government